Energy density of foods and diets in Mexico and their monetary cost by socioeconomic strata: analyses of ENSANUT data 2012. Issue 7 (6th April 2017) - Mendoza, Alfonso; Pérez, Ana E; Aggarwal, Anju; Drewnowski, Adam
Abstract : Background: In January 2014, Mexico implemented an 8% tax on non-essential foods with energy density ≥275 kcal/100 g, with a view to prevent obesity. This study explored energy density of foods and diets in Mexico and their monetary cost across population subgroups. Methods: Dietary intakes for 3057 adults (ages ≥19 years) were obtained from the nationally representative Encuesta Nacional de Salud y Nutrición (ENSANUT 2012). Energy density (kcal/g) was calculated for foods, food groups and total diets. The mean national retail prices for 153 foods were obtained from the National Institute for Geography and Statistics (INEGI). The monetary cost of total diets (MXN/day) was estimated by attaching food prices to dietary intakes from the ENSANUT food frequency questionnaire. A series of descriptive analyses and regression models examined associations among dietary energy density and diet cost by age, gender, rural or urban residence and socioeconomic status (SES). Results: Energy-dense grains, fats and sweets cost less per calorie than did milk and dairy, meat, vegetables and fruit. Lower cost diets derived more calories from tortillas, tamales, beans and sugar, whereas higher cost diets contained more non-essential energy-dense processed foods and more sugar sweetened beverages, and fruits and vegetables. At each quintile of energy intake, higher dietary energy density was associated with lower energy-adjusted diet costs. Traditional energy-dense tortillas and tamales, also characterised by lower cost, were consumed more by the rural poor. Urban dwellers had more 'western-style' diets. Conclusions: Food patterns in Mexico appear to be driven by monetary cost and SES.